2015
DOI: 10.1007/s11199-015-0500-2
|View full text |Cite
|
Sign up to set email alerts
|

“Demonstrating Masculinity” Via Intimate Partner Aggression: The Moderating Effect of Heavy Episodic Drinking

Abstract: The aim of the present study was to examine the mediational effect of masculine gender role stress on the relation between adherence to dimensions of a hegemonic masculinity and male-to-female intimate partner physical aggression. Men’s history of heavy episodic drinking was also examined as a moderator of the proposed mediation effect. A sample of 392 heterosexual men from the southeastern United States who had been in an intimate relationship within the past year completed measures of hegemonic masculine nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
22
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 72 publications
5
22
1
1
Order By: Relevance
“…For the boys in the sample, this aligns with a robust body of work describing male conformity to masculinity norms as a predictor of aggression, violence perpetration, and violence victimization among men . Conformity to masculinity norms in adolescence and young adulthood has also been associated with heavier alcohol use, which raises risk of experiencing or perpetrating violence . One study even found differences in injury‐risk behaviors associated with conformity to masculinity norms in children as young as 3–6 years old .…”
Section: Discussionsupporting
confidence: 70%
“…For the boys in the sample, this aligns with a robust body of work describing male conformity to masculinity norms as a predictor of aggression, violence perpetration, and violence victimization among men . Conformity to masculinity norms in adolescence and young adulthood has also been associated with heavier alcohol use, which raises risk of experiencing or perpetrating violence . One study even found differences in injury‐risk behaviors associated with conformity to masculinity norms in children as young as 3–6 years old .…”
Section: Discussionsupporting
confidence: 70%
“…Contrary to the hypothesis, the result shows that masculine gender role stress does not predict dating violence perpetration. The results are different from the previous research conducted by Reidy et al (2015) and Lisco et al (2015), and indicating the presence of extraneous or mediating variables. Previous research showed that emotion-regulation difficulties mediated these two variables .…”
Section: Discussioncontrasting
confidence: 99%
“…The results suggest that masculine ideology predicts dating violence perpetrated by male college students. These findings are consistent with several previous studies that found the role of masculine ideology as a predictor of intimate partner violence (Lisco et al, 2015). Men who support traditional and rigid values of masculinity tend to engage in more frequent physical violence, sexual violence, and attempt to control their female partners than men who do not adopt traditional masculine values (Casey et al, 2016).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…A meta-analysis of 20 studies supports the theory that MGRS is a significant predictor of IPV (Baugher & Gazmararian, 2015). Further studies have also found that MGRS was positively correlated with the perpetration of intimate partner physical aggression (Lisco, Leone, Gallagher, & Parrott, 2015) and violence in dating relationships (Jakupcak, Lisak, & Roemer, 2002). The studies indicate that men with higher masculine gender role stress were likely to perpetrate an IPV.…”
Section: Psychological Research On Urban Societymentioning
confidence: 74%